Commented checklist of small rodents from Iquitos and its surroundings (Loreto, Peru) - Díaz, María Monica (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The results from surveys of small rodent carried out in 39 collecting sites along the Iquitos-Nauta Highway (Perú), between 2002 and 2005, are presented. Total capture effort was of 18,081 night traps using Sherman traps, 19,271 with Tomahawk, 591 with pitfall traps, and 287 with arboreal traps (Sherman and Tomahawk). The surveys were carried out in three types of environments: primary and secondary forest, and rural area. The results are presented by species indicating distribution, collecting localities, and information about natural history. The greatest capture success was obtained in the arboreal traps (3.83%), followed by the pitfall traps (2.71%), and the traps placed on the ground (1.74%), reflecting the degree of activity of the species in the Amazon canopy. Six hundred and eighty-five rodents, belonging to 25 species, 13 genera, and three families were collected; additionally, information from other 14 species are added in additional records. These results indicate that the studied area can be considered as an area with great diversity of species, being important its conservation, because it is very affected by the increase of the population, agriculture, and the use of wood, which has a negative effect on the species richness and the population dynamics.